Not all roads lead to Rome: the Theory of the Case, its usefulness in oral litigation and a teaching proposal - Elías Puelles, Ricardo (2015)
In recent years, we have seen that the adversarial system has shaped the criminal process in various Latin American countries. This fact leads us to question what are the characteristics of this system, what are the benefits in comparison with the inquisitorial system and which is the method of teaching to which the different procedural actors are exposed.In this article, the author develops in a comprehensive manner the main features of the inquisitorial system and the changing paradigm in Latin American towards the adversarial system, and then explains the influence of this system on the trial lawyer. In addition, it addresses the theory of the case as a methodology that allows to adopt strategic decisions and improve the professional performance of the litigant. Finally, the author explains the necessity of an educational reform asa step in the reform of criminal proceedings.